Lessons learned on establishing laboratory facilities to conduct classes in specialized disciplines while training engineering teaching professionals in the field of the oil and gas industry - Kanyuk, G; Andrуeуеv O; Mezerya, A; Prokopenko, O; Antonenko, N (Problems of Engineer-Pedagogical Education, 2019)
The article presents the experience in creating laboratory facilities to teach courses dealing with studying the equipment for the oil and gas industry and aiming to shape professional competencies while training students specializing in the program subject area 015 "Vocational education(Oil and GasEngineering)" at the Department of Power Engineering and Energy Saving Technologies of Ukrainian Engineering Pedagogics Academy. The main ideas describing a systematic approach to establishing laboratory facilities include: –establishing a laboratory stand at the scale of a real industrial gas distribution station (GDS); –establishing a universal stand of the GDS, including such basic structural elements as a natural gas preparation unit, a gas control unit, a measuring unit for gas consumption, an odorizer, a gas pipeline; –consideringthe specifics and characteristics of operating appliances and measuring equipment used in the oil and gas industry; –developing a set of laboratory experiments used in teaching a number of courses envisaged in the curriculum and aimed at expanding students' knowledge of the characteristics of the oil and gas industry equipment and forming skills for determining its parameters and characteristics, as well as ways to regulate it; –developing didactic support for the classes where the use of the established laboratory facilities is involved; – developing methodological provision for laboratory facilities with regard to the competencies required to become a specialist in the field of the oil and gas industry, specializing in teaching specific courses in the chemical and oil and gas fields, and the requirements for the results of training; – taking into account the specifics of training the teaching staff for the vocational education system; – taking into consideration the requirements on saving energy and resources while developing and establishing laboratory facilities. It is evident that the use of laboratory facilities as a part of the training process ensures that students obtain practical skills for application, adjustment and operation of the equipment used in the oil and gas industry. Mastering the above-mentioned hard skills will enable students to succeed professionally in the future.